Revitalizing Governance of the Indonesian Language for Non-Native Speakers (BIPA) Program at ITB: Enhancing the Internationalization of Indonesian Higher Education - Syuhda, Nisa; Isnaini, Rohmatun Lukluk; Nurdin, Indra Fajar (FKIP Universitas Lampung, 2024)
Revitalizing Governance of the Indonesian Language for Non-Native Speakers (BIPA) Program at ITB: Enhancing the Internationalization of Indonesian Higher Education. Objectives: This study investigates the revitalization of the governance of the Indonesian Language for Non-Native Speakers/Bahasa Indonesia bagi Penutur Asing (BIPA) program at the Bandung Institute of Technology (ITB) in order to achieve World Class University status and enhance the internationalization of higher education in Indonesia. Methods: The study explores the management of the BIPA program, covering aspects such as selection processes, available programs, instructor recruitment and qualifications, student benefits, teaching challenges, and strategies, utilizing qualitative research methods, including thematic analysis, interviews, focus group discussions, and document analysis. Findings: The findings reveal that the BIPA program at ITB is well-structured and funded, with highly qualified instructors, providing international students with opportunities for cultural immersion, career development, and community interaction. Despite challenges such as online learning, linguistic technicalities, and motivational issues, the BIPA program’s success at ITB is attributed to active learning processes, competent teachers, and an ambitious academic culture. Conclusion: The study acknowledges the limitations of focusing on ITB alone and recommends further research on other institutions and programs to contribute more comprehensively to the internationalization of Indonesian higher education. Keywords: BIPA program governance, internationalization; indonesian higher education, world Class University status.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202493